Kualitas Semen Beku Sapi Limousin BIB Tuah Sakato yang Disimpan di Pusat Pembibitan Ternak Sapi Aripan dengan Waktu Thawing yang Berbeda - John Hendri; Harissatria; Syafrizal; Rafi Suryade Putra (Jurnal Peternakan Mahaputra, 2021)
The purpose of this study was to determine the effect of thawing time on the quality of frozen semen of Limousin cattle. This study used an experimental method with a completely randomized design (CRD) with 4 treatments, namely thawing time of 0 seconds, 30 seconds, 60 seconds and 90 seconds at 38oC and 4 replications. The material in this study was frozen semen of 16 straws of Limousin cattle with the same stud code. This research was conducted at the Laboratory of Animal Biotechnology, Andalas University, Padang. From the results of the study, it can be seen that the thawing time of 0 seconds, 30 seconds, 60 seconds and 90 seconds gave a very significant difference (P<0.01) for the percentage of life, percentage of motility and percentage of abnormalities that were thawed at 38oC. It was concludedthat the effect of thawing time of 0 seconds was high on the percentage of motility, percentage of survival and percentage of abnormalities for thawing that could cause spermatozoa (cold shock) or damage.